Improved Heading Direction Interpretation Via Optical Flow Using Selected Region Of Interest - Zainal, Zairulazha; Ramli, Rizauddin; Mustafa, Mohd Marzuki (Elsevier Ltd., 2012)
In this paper, a technique of motion processing and analysis based on optical flow to gather information of heading direction from a vision system is presented. Instead of using the complete frame to determine the heading direction, in this paper, a region of interest (ROI) is used to calculate the heading direction. The selection of this ROI is based on the vector's magnitude dispersion criteria. This value is used as a visual feedback to a control system. The performance of proposed technique is compared to the true heading and the error is evaluated using root mean square error (RMSE). From the results, it shows that by appropriate selection of the region where the information from the optical flow is used, the visual feedback information results in less overshoot and undershoot in terms of its response.